Study on quality enhancement during cigar tobacco fermentation by Staphylococcus nepalensis: insights into microbial community, volatile substances and sensory evaluation - Qi Pei; Qi Pei; Qi Pei; Xue Jiang; Xue Jiang; Xue Jiang; Zhengqin Li; Zhengqin Li; Zhengqin Li; Hong Xu; Hong Xu; Hong Xu; et al. (Frontiers in Microbiology)
BackgroundThe fermentation characteristics of cigar tobacco leaves are closely influenced by the bacterial strains present during the process. This study aims to explore the relationship between bacterial communities and flavor, as well as the impact of key bacterial species on the overall quality of cigars.ResultThe results showed that Staphylococcus nepalensis was the dominant bacteria during the fermentation process. Correlations between bacterial communities and flavor revealed that Staphylococcus nepalensis was positively correlated with carotenoid degradation products, indicating its potential role in promoting flavor formation. Compared to the control groups, those inoculated with Staphylococcus nepalensis showed a significant increase in volatile aroma compounds, particularly megastigmatrienone, and dihydroactinidiolide. Additionally, inoculation with Staphylococcus nepalensis resulted in higher consumption rates of reducing sugars and total nitrogen content. However, nicotine levels were lower in the cigars treated with Staphylococcus nepalensis compared to the controls. The sensory evaluation further revealed that fermentation with Staphylococcus nepalensis notably enhanced the cigars’ aroma quality, reduced irritation, and improved both aftertaste and sweetness.ConclusionIn summary, the study provides valuable bacteriological resources and a theoretical foundation for optimizing industrial production processes, making it useful for enhancing the quality of cigars in large-scale manufacturing.